Effects of entomopathogenic fungi used as plant inoculants on plant growth and pest control - Canassa, Fernanda (2019)
Entomopathogenic fungi (EPF) of the genera Metarhizium and Beauveria are able to endophytically colonize a wide variety of plant species, providing protection against arthropod pests; besides increasing the plant development; and act as phytopathogen antagonists. The main objective of the present project was to evaluate the potential of entomopathogenic fungi as plant inoculants against the two-spotted spider mite Tetranychus urticae and the effects on plant growth promotion. Tritrophic effects were also studied, by evaluating prey consumption and feeding behavior of the predatory mite Phytoseiulus persimilis. The evaluated strategy has several potential benefits compared to the sole use of EPF as contact biocontrol agents, as it may control both pests and phytopathogens; be compatible with other natural enemies; provide limited exposure of fungal propagules to adverse environmental conditions, and accelerate seed emergence and plant growth. Considering this, the effects of seed inoculation using two isolates of Metarhizium robertsii and Beauveria bassiana were evaluated at University of Copenhagen, Denmark, on plant development (i.e. biomass and yield) and T. urticae population growth in a model system with bean plants under greenhouse conditions. Effects on feeding performance of P. persimilis were also studied in laboratory conditions. In Brazil, inoculation studies with EPF were conducted at ESALQ/USP with strawberry plants in greenhouse conditions and in the field in four commercial production areas of strawberries in Atibaia-SP and Senador Amaral-MG. In greenhouse studies, the effects of 15 isolates of Metarhizium spp., 5 isolates of B. bassiana and 5 of Cordyceps (= Isaria) fumosorosea were studied, whereas in the commercial area one isolate of Metarhizium and Beauveria was used. Strawberry roots were inoculated by submersion in fungal suspensions, and the population growth of spider mites, while plants development was assessed by measuring root lengths, biomass of roots and leaves, and the strawberry fruit weight. The results showed a significant reduction in T. urticae population and in general better plant development in both crops. The production of string beans and strawberry fruits were higher in inoculated plants than in non-inoculated plants. There was no difference in predation rate and feeding behavior of the predator mite P. persimilis towards T. urticae from fungal inoculated and uninoculated plants. In the commercial strawberry production areas there were significantly lower populations of T. urticae and fewer symptoms of plant diseases on plants in the fungal treated beds compared to plants in untreated beds. The results of this project bring a new perspective on the use of Metarhizium and Beauveria as plant protecting agents revealing that the use of entomopathogenic fungi as plant inoculants may be a promising strategy.